Staged Isoperistaltic Gastric Tube Esophageal Replacement in Children: A Decade of Experience - J. D. Rawat; Nirpex Tyagi; Sudhir Singh (Journal of Indian Association of Pediatric Surgeons)
Context: Esophageal atresia (EA), with or without tracheoesophageal fistula (TEF), is a rare congenital anomaly. Long-gap esophageal atresia (LGEA) and failed primary repair of TEF often necessitate esophageal replacement in children. This study assesses the outcomes of staged isoperistaltic esophageal replacement using a gastric tube, particularly in resource-limited settings. Aims: The aim of this study was to evaluate the outcomes of staged isoperistaltic esophageal replacement using a gastric tube in children with LGEA and failed primary repair of TEF, particularly in resource-limited settings. Settings and Design: The study was conducted tertiary care hospital, an observational design, spanning 10 years from January 2012 to January 2022. Methods: This study, spanning 10 years (January 2012 to January 2022), focused on pure EA and LGEA with TEF. The three-stage approach included neonatal gastrostomy and esophagostomy, the creation of an isoperistaltic gastric tube at around 10 kg body weight, retrosternal tunneling, and subsequent closure of the cervical esophagostomy. Data on gender, weight, age, complications, gastric emptying, esophageal mucosal status, gastroesophageal reflux, and growth and nutritional status were analyzed. Statistical Analysis Used: The study primarily utilized descriptive statistics to analyze the data. This included reporting means with standard deviations for continuous variables such as weight and age at the time of the second surgery. Results: Twenty-seven cases were studied, with a male-to-female ratio of 3:1. At the second surgery, the mean weight was 9.52 ± 0.56 kg, and the mean age was 8.5 ± 1.25 months. Four cases had minor cervical anastomotic leaks, which were managed conservatively. No postoperative ventilator support was needed. Esophageal stenosis occurred in one case and was managed with endoscopic dilatation. No delayed gastric emptying or Barrett’s esophagus was observed. Growth and nutritional assessments were normal. One mortality occurred due to postoperative bronchospasm. Conclusion: This 10-year study shows that staged isoperistaltic esophageal replacement with a gastric tube is a feasible option for managing EA and LGEA with TEF in resource-limited settings. The technique had low complication rates and supported normal growth and nutrition during follow-up.